Transcriptomic Response Of Salmonella enterica Subspecies enterica serovar Typhi To Antibiotic Treatments During Biofilm Formation - Dashti, Marjan Ganjali (2018)
Salmonella Typhi (S. Typhi) is a human-specific pathogen which causes typhoid fever. One major factor contributing to typhoid persistence is the existence of asymptomatic typhoid carriers. Biofilm formation in the human gallbladder is postulated to be associated with development of the carrier-state. The aim of this study was to develop an optimized assay for S. Typhi biofilm formation in vitro that mimics the environment of the gallbladder. Six key variables involved in S. Typhi biofilm formation were optimized using Response Surface Methodology (RSM), and the resulting assay formed the basis for transcriptomic investigation of biofilm production, in the presence of the antibiotics kanamycin and chloramphenicol.